Detecting ash middens using remote sensing techniques: a comparative study in Southern Gauteng, South Africa - Siteleki, Mncedisi Jabulani (My University, 2016)
The Iron Age is a very critical aspect of South Africa’s history. It represents a technology that laid a solid foundation for the development of South Africa in terms of its economy, politics and society. It is therefore imperative to study Iron Age, or rather its remnants such as stone-walled structures and ash middens because these give insight into this critical time period’s technology and those responsible for it. Remote sensing spatial technology provides the opportunity not only to study these Iron Age remnants but to save time and resources while doing so through satellite imagery. This study employs remote sensing by comparing different multispectral satellite images ̶ GeoEye 1 and SPOT 5 ̶ to find the optimum platform to detect key archaeological remnants  ash middens  from the Iron Age period in the Suikerbosrand Nature Reserve located in Southern Gauteng, South Africa. The performance of GeoEye 1 and SPOT 5 in detecting ash middens was compared through supervised classification techniques, Support Vector Machine and Maximum Likelihood Classification, on different band combinations of the two images. Overall, the band combination of Green, Red and NIR is the best performing on both SPOT 5 and GeoEye 1 compared to Green, Red, and Mid IR on SPOT 5 and Green, Red, and Blue on GeoEye 1. However, higher accuracy of results for the detection of ash middens were obtained on the GeoEye 1 platform. The GeoEye platform performed better than the SPOT platform in the detection and analysis of ash middens. Key Words: Ash Middens, GeoEye, Remote Sensing, Satellite Imagery, SPOT
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. September 2016.
Keywords: Iron age--South Africa--Gauteng, Southern; Remote sensing